2017
DOI: 10.1016/j.oceaneng.2017.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Bearing capacity of spudcan foundations in a spatially varying clayey seabed

Abstract: A B S T R A C TSpudcan foundations are often pushed into a spatially varying non-homogeneous seabed to provide bearing capacity for a mobile jack-up platform. The natural variability of soil properties coupled with the complexity of loading conditions make determining the bearing capacity of spudcan foundations a challenging problem. A random finite element method is established to investigate the bearing capacity of a spudcan foundation embedded in a spatially varying clayey seabed when subjected to vertical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…It has been reported that the horizontal autocorrelation length of marine soil is two orders of magnitude larger than its vertical corresponding length; among which and are between 0.05~14m and 7~9000m [14], respectively, which may be caused by the geological deposition process. The horizontal and vertical correlation lengths for this paper are taken as 50.7m and 3.8m [6,13,14]. However, the diameter of the torpedo anchor is very small relative to the and the range of the mobilized soil during the installation of the anchor is extremely limited in the horizontal direction.…”
Section: Random Fieldmentioning
confidence: 97%
See 2 more Smart Citations
“…It has been reported that the horizontal autocorrelation length of marine soil is two orders of magnitude larger than its vertical corresponding length; among which and are between 0.05~14m and 7~9000m [14], respectively, which may be caused by the geological deposition process. The horizontal and vertical correlation lengths for this paper are taken as 50.7m and 3.8m [6,13,14]. However, the diameter of the torpedo anchor is very small relative to the and the range of the mobilized soil during the installation of the anchor is extremely limited in the horizontal direction.…”
Section: Random Fieldmentioning
confidence: 97%
“…The coefficient of variation (COV)su and the autocorrelation length (θ) are two statistical metrics that quantify the random heterogeneity that is reflected in the random residual. According to research [7,14], the COVsu of clayey soil typically ranges from 0.02 to 0.7. It has been reported that the horizontal autocorrelation length of marine soil is two orders of magnitude larger than its vertical corresponding length; among which and are between 0.05~14m and 7~9000m [14], respectively, which may be caused by the geological deposition process.…”
Section: Random Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Probabilistic methods provide a feasible way to perform real-time optimization for the prediction based on the monitored data. The percentile curves or probabilistic contours of the spudcan load-penetration response can be predicted through Monte Carlo simulations by account-ing for the uncertainties and probabilistic distribution of the inputs in the predictive model [11,[13][14][15]. Bayes' theorem can then be adopted to update these predictions according to the measured load-penetration data [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The wind farm layout optimization is reviewed by Serrano González [5]. Mostly objective functions are the minimization of cost of energy, maximization of the power production, minimization of the blade mass, and so on [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The geometrical, aerodynamic, and physical aspects are to be researched when the constraints are in the field of turbine design.…”
Section: Introductionmentioning
confidence: 99%